Digital Analytical Instruments for Sustainable Growth in Agricultural Sector - V. V. Sukonnikov (Учёт. Анализ. Аудит)
The paper analyzes the contradiction caused by unequal information during agricultural sales, leading to fluctuating prices and affecting both farmers’ profits and product availability. The author suggests a new method to solve this paradox by creating commercial country indices for wheat production and prices using data from modern farm management information systems (FMIS). This paper outlines the development of FMIS in agriculture and examines the factors that both encourage and impede digitalization within the agro-industrial sector. This research identifies leading FMIS providers in the domestic market and analyzes their systems’ capabilities in handling accounting data. The major aim of the paper is evaluating the proposed indices by comparing them to existing price and production indices from prominent market analysts. The author also considers the role of these indicators in the industry’s sustainable development and identifies the limitations of their application. The study resumes that integrating FMIS with state regulatory systems could foster state support for developers of domestic digital systems and agricultural producers who use these analytical tools.